Mother's Motivation On Posyandu Visits And Stunting Incidence In Under Five Years Children Aceh Jaya, Indonesia - Nevi Hasrati Nizami; Sri Agustina; Inda Mariana Harahap (Comprehensive Health Care, 2023)
The inactivity of mothers in participating in visits to Posyandu is caused by various factors that influence mothers' behavior, such as intrinsic motivation and external motivation early. the purpose of this research is to find out the relationship between mother's motivation and Posyandu visits and the relationship between mother's motivation and the incidence of stunting in children under five in the working area of ​​the Calang Health Center, Aceh Jaya district. This type of research is a descriptive correlation with the cross-sectional study method with 173 mothers who have toddlers as respondents; the sampling method uses stratified random sampling, data collection uses a mother's motivation questionnaire, observation sheets of Posyandu visits and toddler height assessment sheets, bivariate research data are analyzed using tests Chi-square.The results showed a relationship between the mother's motivation and Posyandu visits with p-value = 0.000 and a relationship between the mother's motivation and the incidence of stunting with p-value = 0.000. Puskesmas should continue to promote health and hold healthy toddler contests to increase mothers' motivation so that monitoring toddler growth is more optimal.